Molecule-based nonlinear optical switch with highly tunable on-off temperature using a dual solid solution approach - Zhang, Shi-Yong; Shu, Xia; Zeng, Ying; Liu, Qing-Yan; Du, Zi-Yi; He, Chun-Ting; Zhang, Wei-Xiong; Chen, Xiao-Ming (Nature communications, 2020)
Nonlinear optical switches that reversibly convert between on/off states by thermal stimuli are promising for applications in the fields of photoelectronics and photonics. Currently one main drawback for practical application lies in the control of their switch temperature, especially for the temperature range near room temperature. By mixed melting treatment, here we describe an alloy-like nonlinear optical switch with tunable switch temperature via a dual solid solution approach within the coordination polymer system. We initially prepare a coordination polymer ( i -PrNHMe 2 )[Cd(SCN) 3 ], which functions as a high-contrast thermoresponsive nonlinear optical switch originating from a phase transition at around 328 K. Furthermore, by taking advantage of a synergistic dual solid solution effect, the melt mixing of it with its analogue (MeNHEt 2 )[Cd(SCN) 3 ], which features an unequal anionic chain templated by an isomeric ammonium, can afford coordination polymer solid solutions with switch temperatures that are tunable in a range of 273–328 K merely by varying the component ratio. Switching of nonlinear optical signals is attractive for photoelectronics and photonics, but development is hindered by a lack of control over the switch temperature. Here the authors report a coordination polymer system that serves as an alloy-like nonlinear optical switch with a tunable switch temperature.